2000
DOI: 10.1590/s0004-282x2000000300009
|View full text |Cite
|
Sign up to set email alerts
|

Interferon beta 1-a na esclerose múltipla: experiência de um ano em 62 pacientes

Abstract: RESUMO -Relatamos os resultados de estudo com o interferon beta 1-a em 62 pacientes ambulatoriais com a forma remitente-recorrente da esclerose múltipla durante um ano. Os critérios de inclusão para este tratamento foram de escore do EDSS entre 0 e 5,5 e de pelo menos relato de dois surtos nos dois últimos anos. Administramos 3 milhões de unidades internacionais de interferon beta 1-a três vezes por semana. Os objetivos deste estudo foram verificar o efeito da medicação no número de surtos e avaliar a eficácia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…This investigation, carried out in the reference center for MS of the State of Bahia, showed that, in spite of MS being an urban disease, with well-defined diagnostic criteria, the medical and epidemiological features of the disease vary according to the geographical area under investigation, as we can see from the different Brazilian states [4][5][6][7][8][9][10][11][12][13] . Thus, while we estimate a prevalence of less than 5% for the Northeastern region 5% 6,13 , prevalence in the Southern and Southeastern regions range between 15% to 18% 4,5,[7][8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This investigation, carried out in the reference center for MS of the State of Bahia, showed that, in spite of MS being an urban disease, with well-defined diagnostic criteria, the medical and epidemiological features of the disease vary according to the geographical area under investigation, as we can see from the different Brazilian states [4][5][6][7][8][9][10][11][12][13] . Thus, while we estimate a prevalence of less than 5% for the Northeastern region 5% 6,13 , prevalence in the Southern and Southeastern regions range between 15% to 18% 4,5,[7][8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while we estimate a prevalence of less than 5% for the Northeastern region 5% 6,13 , prevalence in the Southern and Southeastern regions range between 15% to 18% 4,5,[7][8][9][10][11][12] . On the other hand, the higher frequency of the optical pathways and the spinal marrow as the site of first symptoms observed in this study confirm data from other Brazilian authors, who point a higher proportion of Devic's disease among black-colored individuals, and Lana-Peixoto 7 stressed out similarities with the Asian type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first articles on the immunology of the disease in Brazil 2,3 . The first Brazilian clinical trials and guidelines on the treatment of MS with beta-interferon 6,7 .…”
mentioning
confidence: 99%